Effects of Flash Sintering Parameters on Performance of Ceramic Insulator - Yong Liu; Xingwang Huang (Energies, 2021)
Ceramic outdoor insulators play an important role in electrical insulation and mechanical support because of good chemical and thermal stability, which have been widely used in power systems. However, the brittleness and surface discharge of ceramic material greatly limit the application of ceramic insulators. From the perspective of sintering technology, flash sintering technology is used to improve the performance of ceramic insulators. In this paper, the simulation model of producing the ceramic insulator by the flash sintering technology was set up. Material Studio was used to study the influence of electric field intensity and temperature on the alumina unit cell. COMSOL was used to study the influence of electric field intensity and current density on sintering speed, density and grain size. Obtained results showed that under high temperature and high voltage, the volume of the unit cell becomes smaller and the atoms are arranged more closely. The increase of current density can result in higher ceramic density and larger grain size. With the electric field intensity increasing, incubation time shows a decreasing tendency and energy consumption is reduced. Ceramic insulators with a higher uniform structure and a smaller grain size can show better dielectric performance and higher flashover voltage.